Type 2 diabetes mellitus and gout - O. V. Zhelyabina; M. S. Eliseev (Научно-практическая ревматология)
Gout is the most common inflammatory arthritis in adults and has continued to increase in prevalence over the past decades. Gout is characterized by hyperuricemia with the obligatory crystallization of urates and an associated inflammatory reaction, as well as metabolic effects caused, among other things, by these processes. In particular, the diagnosis of gout is identified with a high risk of carbohydrate metabolism disorders, which is 2 times higher than the population risk: according to various sources, from 21 to 26% of patients with gout have type 2 diabetes mellitus (DM 2). However, the role of uric acid and urate-lowering drugs in its development in patients with gout remains controversial. The possibility of influencing the risk of developing diabetes mellitus type 2 of chronic inflammation, the activity of interleukin-1β and other pro-inflammatory cytokines, hyperuricemia, xanthioxidase and other factors associated with gout is discussed. It is possible that the level of uric acid is associated with diabetes and other metabolic diseases, causing pathophysiological changes not only through inflammation, but also oxidative stress, damage to the vascular endothelium. It is also suggested that gout and DM 2 may share genetic markers. The interrelation of violations of purine and carbohydrate metabolism prompts the search for drugs that have a simultaneous positive effect on purine and carbohydrate metabolism. However, it is not clear what the level of uric acid should be considered as a risk factor, there are conflicting data on the possibility of reducing the risk of developing diabetes with various anti-gout therapies.